TRANSFORMASI PANDANGAN PERDAGANGAN INTERNASIONAL AMERIKA SERIKAT DI ERA GLOBALISASI - Martha Damai Mayasari (Dauliyah Journal of Islamic and International Affairs, 2019)
Globalization is a phenomenon that cannot be avoided. Globalization of trade causes the trade economy of a country to be directly distributed quickly to other countries which causes the existence of international trade and free markets. The United States is a country that was initially very supportive and optimistic about globalization. All policies support globalization. As time goes on due to differences in situations and conditions in the world resulting in a shift in the view of the United States towards the existence of international trade. This paper aims to provide an overview of the transformation of the shift in America's view of globalization. Through a study of a number of literatures, the authors found that America's view of trade globalization experienced changes in the thinking of leaders and society towards the values and effects brought about by the current globalization in this era.